Outcome of rhegmatogenous retinal detachment repair: Experience of a tertiary center in Oman - Ahmed S Al-Hinai (Oman Journal of Ophthalmology, 2013)
Aim: To study the outcome of repair of rhegmatogenous retinal detachment (RRD) in a tertiary center. Design: Retrospective study. Materials and Methods: Review of electronic medical records within a period of 29 months of consecutive patients who underwent surgical repair for RRD in Sultan Qaboos University Hospital (SQUH). Results: We included 33 consecutive patients (36 eyes). Males constituted 70% of them. The average age was 47 years. Seven eyes out of the 36 had macula-on RRD at presentation. The primary success rate with a single procedure was 86%. However, redetachment occurred in five eyes (14%). Visual acuity was either same as preoperative or better in 81% of the eyes. Giant retinal tear was found in three eyes (8%). The average follow-up period for all patients was 10.25 months (range: 3-25 months). Conclusion: Rhegmatogenous RD is not uncommon disorder. It occurs more frequently in males. However, it has a good prognosis if an intervention was performed in early stages.